Confronting experimental error in industrial DOE: A fresh look. Issue Volume 34:Issues 4(2022) (29th November 2022) - Grima, Pere; Marco-Almagro, Lluís; Tort-Martorell, Xavier
Abstract: In this quandary, we argue that three frequent situations in the design of experiments: blocking, robustness, and hard-to-change factors emerged in intervals over time and were integrated into the "science" of designing experiments as they came along. Following De Bono's 1992 idea of escaping the "time sequence trap", we review them and propose a fresh way of approaching them.